Landasan Filosofis Bimbingan Keterampilan Berbahasa Indonesia Bagi Siswa Sekolah Indonesia Davao Filipina - Yunia Tiara Riski; Huda, Muhammad; Budi Purwoko; Ganes Gunansyah (AIJER: Algazali International Journal Of Educational Research, 2024)
In the 21st century, communication skills have become the main competency that must be possessed to face global challenges and build national identity. The Indonesian School of Davao (SID) provides Indonesian language tutoring for students born and raised in the Philippines. This article aimed to review these guidance activities from the perspective of the philosophy of science, covering practical, theoretical, and philosophical foundations, as well as their contribution to students and teachers in the educational context at SID. Researchers used the library study research method, which uses library materials or literature as the main source of information. The results showed that language guidance and literacy programs practically helped students adapt to a multilingual environment and strengthen national identity. In theory, language learning is based on language acquisition theory which emphasizes the importance of social interaction, reinforcement, and contextual learning to motivate students. Philosophically, the Indonesian language is seen as a symbol of national identity, which is the main means of instilling national values, shaping students' character, and preparing them to contribute to global society.